Self-acceptance in fatherless early adult women due to parental divorce - Salmanina Hapsari; Suryanto Suryanto (University of Merdeka Malang, 2025)
Losing father’s role or what called “fatherless” due to parental divorce can be occurred by early adults. Early adulthood is a phase where individual tends to explore their identity. For women, exploring identity cannot be separated from environmental factors and closed ones, including her father. If an early adult woman loses her father figure in her life, it will be impacted on psychological factors and the process of self-acceptance. This study aims to see the self-acceptance in early adult women who experience fatherlessness due to parental divorce. The research method used is qualitative with a phenomenological approach. Data collection using in-depth interviews in early adult women who experience fatherless due to parental divorce. The data analysis technique uses Interpretative Phenomenology Analysis (IPA). The results of the study showed that there are several aspects that can form self-acceptance in early adult women who experienced fatherless due to parental divorce, such as self-understanding, sincerity, perceived improvements in quality of life, resilience and coping strategies, social support, and self-expectation.